Order and hyper-order of entire solutions of linear differential equations with entire coefficients. - Belaıdi, Benharrat; Hamani, Karima (Electronic Journal of Differential Equations (EJDE)[electronic only], 2003)
Line 1 overbar dens sub E= limint r right arrow plus infinity supremum m open parenthesis E cap open square bracket 0 comma r closing square bracket closing parenthesis divided by r sub comma dens underbar to the power of E= limint r right arrow plus inf infinity m open parenthesis E cap open square bracket 0 comma r closing square bracket closing parenthesis divided by r sub period open parenthesis 1 period 3 closing parenthesis Line 2 hline* sub Mathematics Subject Classifications: 30 D 35 comma 34 M 10 comma 34 C 1 1 period
Keywords: Linear differential equations; growth of entire functions; hyper-order; circlecopyrt - c2003